Pengembangan Nilai Moral Anak Usia Dini melalui Metode Pembiasaan di RA Al-Jabbar Kota Batam - Ismawaty, Qory (Indonesian Journal of Islamic Early Childhood Education, 2017)
The purpose of this research is to know the implementation of moral value development to early childhood. This research was conducted in RA Al-Jabbar Batam City, involving 20 children consist of 13 boys and 7 girls enrolled in academic year 2016/2017 belonging to group B. The method used in this research is qualitative. Instruments for collecting data are through observation, interview and documentation. Data validity is checked by triangulation. The data were analyzed by using critical analysis and qualitative comparative analysis and interview, then processed descriptively by using assessment criteria transferred into quantitative form to know the result of development of moral values ââof children through method of habituation. The results showed that with the method of habituation, the moral values ââof children have developed. The conclusion of this study is the moral values ââof early childhood in RA Al-Jabbar Batam City can be developed through the habituation method.